2016
DOI: 10.1021/acs.est.6b00632
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Photoelectrocatalytic Decomplexation of Cu–EDTA and Cu Recovery by Persulfate Activated by UV and Cathodic Reduction

Abstract: In order to enhance Cu−EDTA decomplexation and copper cathodic recovery via the photoelectrocatalytic (PEC) process, S 2 O 8 2− was introduced into the PEC system with a TiO 2 /Ti photoanode. At a current density of 0.2 mA/cm 2 and initial solution pH of 3.0, the decomplexation ratio of Cu complexes was increased from 47.5% in the PEC process to 98.4% with 5 mM S 2 O 8 2− addition into the PEC process (PEC/S 2 O 8 2− ). Correspondently, recovery percentage of Cu was increased to 98.3% from 47.4% within 60 min.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
48
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 140 publications
(48 citation statements)
references
References 40 publications
0
48
0
Order By: Relevance
“…However, the mechanism remained unclear about the interaction between PS and PEC reaction. Zeng et al reported that PS was added to a photoelectrocatalytic system driven by UV light in order to enhance the Cu-EDTA decomplexation and Cu recovery [25]. This paper indicated the PS activation through cathodic electron and served as a bridge between two techniques.…”
Section: ð1þmentioning
confidence: 90%
“…However, the mechanism remained unclear about the interaction between PS and PEC reaction. Zeng et al reported that PS was added to a photoelectrocatalytic system driven by UV light in order to enhance the Cu-EDTA decomplexation and Cu recovery [25]. This paper indicated the PS activation through cathodic electron and served as a bridge between two techniques.…”
Section: ð1þmentioning
confidence: 90%
“…Recently, persulfate (PS), a kind of oxidant agent, was used for in situ chemical oxidation in the remediation of organic pollutants in aqueous systems (Ahmad et al, 2013;Hazimea et al, 2013). A large number of studies showed that PS can be active by UV, heat, alkaline, transition metals to produce sulfate radicals (SO 4 À ) and hydroxyl radicals ( OH) (Chen and Huang, 2015;Hazimea et al, 2013;Waldemer et al, 2007;Zeng et al, 2016;Hu et al, 2016), which have high redox potential and can destroy most of organic compounds efficiently. Hu and tian investigated the g-C 3 N 4 /Fe(III)/ PS system which found that the phenol degradation efficiency can be significantly improved by combing photocatalysis and light Fenton interaction (Hu et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The successful deposition of Cu onto the NF can be verified by the Cu 2p XPS spectra. As displayed in Figure S4d, the signals located at 931.8 eV and 953.0 eV were assignable to the emissions from Cu 2p 3/2 and Cu2p 1/2 levels, which corresponded to the typical binding energy of Cu 0 [19]. Other binding energies present at 934.4 eV for Cu 2p 3/2 and 954.0 eV for Cu 2p 1/2 were ascribed to Cu 2+ [6,20].…”
Section: Characterizationsmentioning
confidence: 90%